Distributed cybersecurity strategy, applying intelligence operation concept through data collection and analysis - Gallardo Urbini, Ignacio Martín; Bazán, Patricia Alejandra; Venosa, Paula; Río, Nicolás del (2021)
This document presents a line of doctoral research that proposes a cybersecurity strategy that has not been formally standardized up to now, based on knowledge of defense intelligence operations, and applying a dynamic approach, in a context of threat risk, anticipating its effectiveness . In this way, change the current approach, leaving aside the old concept of "walled" defense, for a more innovative one, where information collectors or "spies" infiltrate "unknown terrain" or external networks to extract data and information, learn from context, analyze and detect patterns, be willing to share the knowledge, and then be able to make defensive, deterrent, or offensive decisions in real time.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Jornadas de Cloud Computing, Big Data & Emerging Topics (9na : 2021 : La Plata, Argentina)
Keywords: BIG DATA; SEGURIDAD Y PROTECCIÓN